(3fXQjGJ GdEQTGO GdJQHhjs - (3GdHGhj, Ydj gGTe LGhTs ((3HjQhJs (3eDSSI GdhQGbs, 2011)
(3oJYJHQ GdYedjI GdJYdjejI ef CYXe GdCYeGd eTnqbI Ydi fahS GdeYdejf hGdeYdeGJ, hgj oJYqO aj GdhbJ faSg, ef CcKQ GdhXGFa faGPkG Edi GdbdhH GdNqjQI hGdYbhd GdfqjQI, HGYKI aj cd efgG SYGOI hCedkG jYLR Gdbde Yf GdJYHjQ YfgeG, dCf eSJbHd GdChWGf jJYdb HGdCLjGd GdJj JJYgOgG CjOj GdeYdejf hGdeYdeGJ, HGdQYGjI GdcGedI hGdEgJeGe GdhGSY, aef ojYqO CHfGA GdReGf GdbGOejf Ydi CLfMI GdfShQ, aj YUQ JgGhJ ajg MhGLR GdecGf hSOhO GdReGf, jTqjO deSJbHd GdHTQjI bdGYkG eMqUfI, hMUhfkG efjYI, hjQaY ddaNGQ CHQGLkG JdGeS gGe GdqSMGH(B. (3Ef UfGYI GdYbhd GdHTQjI, djSJ CeQkG gqjfkG Ydi fahS QLGd GdJQHjI hGdJYdje, dCfgG JaQV HbqhI JMJ Yde GdeSDhdjI, LhOI GdEYOGO, hEJbGf GdYed, hSdGeI GdJUqQa, hGqJSGY GdKbGaI, hJNqdd GdYdhe hGdeYGQa hGdBOGH hGdafhf, dEeOGO CTQa GdfGS, OhQkG hJhLjgkG hJQHjI hYdekG, Hcqd RGO NqjQ, heDhfI eKeQI, dG jVjY faYgeG eY eQhQ GdCjGe hJbqdHGJ GdCRefI hGdqOghQ(B. (3hcJGH GdJOQjH hGdJOqQH Ydi GdeTGgOI hGdeTGQcI hGdeeGQSI, gh cJGH Ydej aj ehVhYGJg, efgLj aj JSdSdg hJQGHWg, gOag Cf jVY CeGe GdWdGH hGdWGdHGJ aj cdjGJ GdJQHjI, CVhGA gGOjI Edi WQjb LhOI GdEYOGO, heJGfI GdESJYOGO dCOhGQge GdJYdejI Gdjhe, hdeSJbHdge GdhXjaj ZOkG, hCf jYqQage Edi egGqege heSDhdjGJge hhGLHGJge GdJj SJdbi Ydi chGgdge aj GdCjGe GdbGOeI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Orientation et Conseil; School guidance and counseling; (3GdJhLjg hGdEQTGO GdeOQSjs